Analisis Strategi Pemasaran Dalam Upaya Peningkatan Daya Saing Pada ES Teh Indonesia Cabang Lamongan - Muhamad Taufik (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The purpose of this study is to analyze the application of marketing strategies in an effort to increase competitiveness at the Lamongan branch is precisely on the Basuki Rahmat street of Indonesian Ice Tea. The approach used in this research is a descriptive approach with qualitative methods. The type of data used is primary data and secondary data. The research technique that the author uses to collect data in this study is through observation or interviews. The analysis used in this research is SWOT analysis. From the results of this study, the marketing strategy carried out by Indonesian Ice Tea is that they cooperate with Go-Jek, Grab, Drivers in the Lamongan area, apart from selling them offline by directly coming to the outlet, and Indonesian Ice Tea also sells its products online. online through social media, one of which is through the Instagram platform. Based on the SWOT analysis conducted on Indonesian Ice Tea, several marketing strategies have been formulated in an effort to increase competitiveness, including by maintaining product quality, expanding marketing areas, continuing to innovate in various flavors, and optimally utilizing marketing promotion media from various social media